A new survey of the serology of human Trypanosoma cruzi infection in the Rio Negro microregion, Brazilian Amazon: a critical analysis - Jose Rodrigues Coura; Mauricio Humberto Pena Marquez; Jorge Augusto de Oliveira Guerra; Patricia Lago Zauza; Julio Cesar Miguel; Jose Borges Pereira (Memorias do Instituto Oswaldo Cruz, 2013)
The serology of human Trypanosoma cruzi infection in the Rio Negro microregion is very complex because of the large numbers of false-positive cases that result from low antibody titres and cross-reactions with other infections. In the present study, we collected 4,880 blood samples on filter paper; of these, indirect immunofluorescence (IIF) was strongly reactive in 221 (4.5%), which were considered to be positive (IIF strongly reactive; high intensity of fluorescence) and weakly reactive in 302 (6.2%), which were considered to be doubtful (IIF weakly reactive; low intensity of fluorescence). The confirmatory test on the serum using at least two of three techniques (IIF, conventional ELISA and recombinant ELISA) on 137 samples that were positive in the screening test only confirmed 33 cases (24.1%). Of the 178 samples that were considered doubtful in the screening test, only 10 (5.6%) were considered to be positive in the confirmatory test. Finally, we recommend that the serological diagnosis of T. cruzi infection in the Amazon region be made using at least two different techniques, for example immunofluorescence and ELISA and confirmed by Western blot analysis when possible.